The Effect of Low Ambient Relative Humidity on Physical Performance and Perceptual Responses during Load Carriage - Mekjavic, Igor B.; Ciuha, Ursa; Grönkvist, Mikael; Eiken, Ola (Frontiers in physiology, 2017)
The study evaluated the effect of low ambient relative humidity on physical performance and perceptual responses during load carriage in a hot environment. Ten heat-unacclimatized male subjects participated in three 130-min trials, during which they walked on a treadmill, carrying a load of ~35 kg, at a speed of 3.2 km.h , with an incident wind at the same velocity and ambient temperature at 45°C. Each trial commenced with a 10-min baseline at 20°C and 50% relative humidity (RH), the subjects transferred to a climatic chamber and commenced their simulated hike, comprising two 50-min walks separated by a 20-min rest period. In two, full protective equipment (FP) trials, RH was 10% (partial pressure of water vapor, p = 7.2 mmHg) in one (FP10), and 20% (p = 14.4 mmHg; FP20) in the other. In the control trial, subjects were semi-nude (SN) and carried the equipment in their backpacks; RH was 20%. Measurements included oxygen uptake, ventilation, heart rate, rectal and skin temperatures, heat flux, temperature perception, and thermal comfort. In FP20, four subjects terminated the trial prematurely due to signs of heat exhaustion; there were no such signs in FP10 or SN. Upon completion of the trials, pulmonary ventilation, heart rate, and rectal temperature were lower in FP10 (33 ± 5 l/min; 128 ± 21 bpm; 38.2 ± 0.4°C) and SN (34 ± 4 l/min; 113 ± 18 bpm; 38.1 ± 0.4°C than in FP20 (39 ± 8 l/min; 145 ± 12 bpm; 38.6 ± 0.4°C). Evaporation was significantly greater in the SN compared to FP10 and FP20 trials. FP10 was rated thermally more comfortable than FP20. A lower ambient partial pressure of water vapor, reflected in a lower ambient relative humidity, improved cardiorespiratory, thermoregulatory, and perceptual responses during load carriage.